MediaTIC: A Social Media Analytics Framework For the Costa Rican News Media - Soto-Rojas, Cristina (2020)
Social media sites such as Facebook are tools that democratize contents. These tools facilitate the creation of news and ideas. In Costa Rica, we designed MediaTIC framework to track social media outlets communities by accessing their posts and user interactions. In order to do this, we created a big data store and designed a software architecture that uses high computing hardware (cluster) to manage software escalation, data volume, and future requirements. We used MongoDB, Spark and R technologies to build the platform and manage the information. This platform, allowed us to run faster queries, improving the performance time in 110%-180% approximately. The main objective is to provide visualizations and information for Costa Rican social media analysts that can give value to Social Communication Science in Costa Rica by using high technology underneath.